Bond between near-surface mounted carbon-fiber-reinforced polymer laminate strips and concrete - Sena-Cruz, José (2004)
In recent years, a strengthening technique based on near-surface mounted (NSM) laminate strips of carbon-fiber-reinforced polymer (CFRP) has been used to increase the load-carrying capacity of concrete and masonry structures by introducing laminate strips into precut grooves on the concrete cover of the elements to be strengthened. The high experimentally derived levels of strength efficacy with concrete columns, beams, and masonry panels have presented NSM as a viable and promising technique. This practice requires no surface preparation work and, after cutting the groove, requires minimal installation time compared to the externally bonded reinforcing technique. A further advantage associated with NSM CFRP is its ability to significantly reduce the probability of harm resulting from fire, acts of vandalism, mechanical damage, and aging effects. To assess the bond behavior of CFRP to concrete, pullout-bending tests have been carried out. The influences of bond length and concrete strength on bond behavior are analyzed, the tests are described, and the results are presented and discussed in detail. Finally, a local stress-slip relationship is determined based on both experimental results and a numerical strategy.